(untitled) (CIPEEX, 2025)
This study highlights the remarkable technological advances that have been incorporated into the operations of financial institutions, while also highlighting the challenges faced by the elderly in adapting to these innovations. It also highlights the importance of public policies to ensure digital inclusion, with special attention to trust as a crucial factor in this integration process. To explore these issues in more detail, field research will be carried out in the São Patrício Valley region, with the aim of closely examining users’ perceptions of the relationship between the use of technology and age, especially in the context of financial institutions. The methodology will be based on the application of a comprehensive electronic questionnaire with volunteers who declare themselves to be residents of any of the cities in the São Patrício Valley, followed by a thorough statistical analysis of the data collected, with the aim of identifying patterns of behavior related to the adoption of technology in financial institutions by different age groups, and will apply quantitative methodology.A sample calculation will be carried out, and some tools will be used to assist in data collection, organization and presentation of the results. The central focus of this study is to provide valuable insights for the development of more effective public policies, while contributing to a more comprehensive and in-depth understanding of the local scenario in question. It is hoped that this research will demonstrate how the age of users affects their perception and adoption of digital environments in financial institutions in the São Patrício Valley.